40. PATTERN OF CARDIOVASCULAR DISEASE IN THE ELDERLY INPATIENTS AT THONG NHAT HOSPITAL IN HO CHI MINH CITY IN 2022 (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the pattern of cardiovascular disease in the elderly at Thong Nhat Hospital in Ho Chi Minh city in 2022.Methods: A cross-sectional study including 10,546 elderly inpatients (≥ 60 years old) with cardiovascular disease at Thong Nhat Hospital in Ho Chi Minh city from January 1, 2022 to December 31, 2022. Results: Elderly inpatients with cardiovascular disease at Thong Nhat Hospital are evenly distributed across three age groups (60-69, 70-79 and ≥ 80), while the proportion of male patients (52.91%) is higher than those of female patients (47.09%). The most common cardiovascular diseases are hypertension (72.44%), arrhythmia (40.58%), heart failure syndrome (19.47%) and cerebrovascular disease (11.58%). There was no difference in the pattern of cardiovascular disease in different age groups and gender. The risk factors of cardiovascular disease in the elderly inpatients were aged ≥ 70 years, pre-obesity or obesity, abnormal WHR index, alcohol or beer drinking, smoking, dyslipidemia and diabetes.Conclusion: Hypertension, arrhythmia, heart failure and cerebrovascular disease are common cardiovascular diseases in the elderly.
Keywords: Cardiovascular diseases; the elderly; disease patterns